Pure Vibrant Colours, Golden Groundings, and Red Scenery – Various Approaches in the Use of Colours in Medieval Times (KULT_online, 2012)
This two volume collection of 70 essays brings together the work of medievalists from various disciplines. While dealing with 'colour' as a comprehensive topic, these medievalists employ multifaceted perspectives. Hence, their objects of study differ and they favour different approaches to explore these objects. Their foci include the acquisition and processing of some pigments in mediaeval times, a search for the material and ideal value, and a look into the possible meanings of colour in concrete contexts. In addition, these medievalists are also interested in the etymological derivations of colour terms, the terminology of recipe books, and the functionalisation of colours in literary texts.